CLINICAL FACTORS FOR DEVELOPING SHOCK IN RADIOCONTRAST MEDIA INDUCED ANAPHYLAXIS. Issue 3 (March 2016) - Kim, Sang Min; Ko, Byuk Sung; Kim, Ji Yeon; Ha, Sang Ook; Ahn, Shin; Sohn, Chang Hwan; Seo, Dong Woo; Kim, Tae-Bum; Kim, Won Young
Abstract : ABSTRACT: The aim of this study was to investigate the time interval between radiocontrast media (RCM) administration and the development of anaphylactic shock, and risk factors associated with RCM-induced anaphylactic shock. We reviewed the medical records of 154 patients with RCM-induced anaphylaxis presenting to the emergency department of a tertiary care hospital between January 2005 and December 2014. Clinical features of RCM-induced anaphylaxis were analyzed, and patients were categorized into shock and non-shock groups to identify associated factors in affected patients. Of the 154 cases of RCM-induced anaphylaxis, 101 (65.9%) patients experienced shock. The median time between RCM exposure and the onset of shock was 11 min (interquartile range, 7.0–18.8). In patients with RCM-induced anaphylaxis accompanying shock, the median time from RCM to the first symptom onset was 6 min (interquartile range, 5.0–10.0). In the multivariate analysis, age, neurological manifestations, and allergy history except RCM were associated with the development of shock. RCM-induced anaphylaxis was commonly accompanied with shock, and the time interval between RCM exposure and the onset of shock was short. Physicians should pay attention to the development of potential cardiovascular collapse in anaphylaxis patients of old age and with neurologic manifestations.